Pengaruh Personal Attribute, Environmental, Sociological dan Entrepreneurship Education Terhadap Minat Berwirausaha Mahasiswa FEBI IAIN Ponorogo - Indri Devi Antikalestari; Estu Unggul Drajat (Niqosiya: Journal of Economics and Business Research, 2024)
Entrepreneurship is a good and very important way of financial management. Even though many students are focused on academics or organizations only, students are relatively vulnerable to the temptation of fashion, trends and lifestyles which can increase students' opportunities in matters of personal financial management, and the majority of students are still dependent on their parents and do not have their own income, students should be able to learn entrepreneurship and good financial management. The aim of this research is to test and analyze the influence of personal attribute, environmental, sociological and entrepreneurship education factors on FEBI IAIN Ponorogo students' entrepreneurial interest partially and simultaneously. This research is quantitative research. This research uses primary data where data collection uses questionnaires and interviews. The objects of this research are FEBI IAIN Ponorogo students who have taken the Entrepreneurship course. From this research, results were obtained: Sig value was obtained. 0.000 < 0.05 proves that the personal attribute factor has a positive and significant effect on the variable interest in entrepreneurship, the results of the sig value. 0.000 < 0.05 proves that environmental factors have a positive and significant effect on the variable interest in entrepreneurship, the results of the sig value. 0.063 > 0.05 proves that sociological factors have no influence on the variable interest in entrepreneurship, the results of the sig. 0.249 > 0.05 proves that the entrepreneurship education factor has no influence on the entrepreneurial interest variable and the results of the f test show that the value of f-count (85.950) > f-table (2.40) shows that the personal attribute, environmental, sociological and entrepreneurship education factor variables have a positive effect. and simultaneously significant for the entrepreneurial interest variable of FEBI IAIN Ponorogo students